Hydroxyethyl cellulose-grafted loofa sponge-based metal affinity adsorbents for protein purification and enzyme immobilization. (November 2018) - Lai, Wei-Jie; Lin, Sung-Chyr
Graphical abstract: Highlights: Loofa sponge-based IMAC adsorbents for protein purification was prepared. Grafting of hydroxyl ethylcellulose (HEC) increased the capacity of the adsorbents. Co(II)-loaded loofa sponge-HEC-IDA exhibited superior adsorption selectivity. Enzyme immobilized with the adsorbent retained 70% activity after 20 cycles. Abstract: The development of loofa sponge-based immobilized metal affinity adsorbents was reported in this study. We showed that by grafting hydroxyethyl cellulose (HEC) to loofa sponge the chelating capacity was increased by 117% from 2520 ± 45 μmole/g to 5478 ± 77 μmole/g. Results of equilibrium adsorption study showed that the adsorption capacity of the HEC-grafted loofa sponge-based immobilized metal affinity adsorbent for the recombinant His-tagged trehalose synthase, 2.45 mg/g, was 62% higher than that of the adsorbent without HEC conjugation, 1.51 mg/g. The employment of the trehalose synthase-loaded loofa sponge-based immobilized metal affinity adsorbent as the biocatalyst for the conversion of maltose to trehalose in repeated-batch operations was conducted. It was found that after 20 cycles 70% of the initial activity was retained. The decline in activity could be attributed predominantly to the desorption of trehalose synthase from the loofa sponge-based immobilized metal affinity adsorbent.